Profitability and Market Value Effect on Carbon Emission Disclosures: The Moderating Role of Environmental Performance - Fitra Dharma; Maran Marimutu; Liza Alvia (International Journal of Energy Economics and Policy)
Climate change is an issue that is of concern to the global public and scientific community. There is a close relationship between climate change and carbon emissions, which are the primary cause of global warming. Reporting on carbon emissions is essential for corporate accountability to stakeholders when evaluating a company's financial and non-financial performance. Good management of carbon emissions will enhance the company's reputation. This study analyses the impact of company profitability and market value on the disclosure of carbon emissions, with environmental performance serving as a moderating variable in the context of Indonesian public companies. This study concludes that: (1) There is no significant impact on profitability, as measured by Return on Assets, on Carbon Emission Disclosure; (2) The study finds that there is a statistically significant positive relationship between market value, measured by Tobin's Q, and the level of carbon emission disclosure. This relationship is significant at a 5% significance level; (3) The moderating effect of environmental performance on the relationship between profitability, as measured by return on assets, and carbon emission disclosure is found to be insignificant; (4) The significance level of 10% indicates that the relationship between environmental performance, as a measure of a company's environmental practices, and market value, as represented by Tobin's Q, is strengthened concerning the disclosure of carbon emissions. This research can contribute to developing accounting knowledge to close gaps in the body of knowledge regarding the disclosure of carbon emissions in developing nations, particularly Indonesia.